Development of disease-resistant rice using regulatory components of induced disease resistance - Takatsuji, Hiroshi (Frontiers in Plant Science, 2014)
Infectious diseases cause huge crop losses annually. In response to pathogen attacks, plants activate defense systems that are mediated through various signaling pathways. The salicylic acid (SA) signaling pathway is the most powerful of these pathways. Several regulatory components of the SA signaling pathway have been identified, and are potential targets for genetic manipulation of plants’ disease resistance. However, the resistance associated with these regulatory components is often accompanied by fitness costs; that is, negative effects on plant growth and crop yield. Chemical defense inducers, such as benzothiadiazole and probenazole, act on the SA pathway and induce strong resistance to various pathogens without major fitness costs, owing to their ‘priming effect’. Studies on how benzothiadiazole induces disease resistance in rice have identified WRKY45, a key transcription factor in the branched SA pathway, and OsNPR1/NH1. Rice plants overexpressing WRKY45 were extremely resistant to rice blast disease caused by the fungus Magnaporthe oryzae and bacterial leaf blight disease caused by Xanthomonas oryzae pv. oryzae (Xoo), the two major rice diseases. Disease resistance is often accompanied by fitness costs; however, WRKY45 overexpression imposed relatively small fitness costs on rice because of its priming effect. This priming effect was similar to that of chemical defense inducers, although the fitness costs were amplified by some environmental factors. WRKY45 is degraded by the ubiquitin–proteasome system, and the dual role of this degradation partly explains the priming effect. The synergistic interaction between SA and cytokinin signaling that activates WRKY45 also likely contributes to the priming effect. With a main focus on these studies, I review the current knowledge of SA-pathway-dependent defense in rice by comparing it with that in Arabidopsis, and discuss potential strategies to develop disease-resistant rice using signaling components.